Influence of additives on the electrodeposition of zinc from a deep eutectic solvent. (1st May 2019) - Alesary, Hasan F.; Cihangir, Salih; Ballantyne, Andrew D.; Harris, Robert C.; Weston, David P.; Abbott, Andrew P.; Ryder, Karl S.
Abstract: The effects of nicotinic acid (NA), boric acid (BA) and benzoquinone (BQ) on the electrodeposition of Zn have been studied in a choline chloride (ChCl) ethylene glycol (EG) based deep eutectic solvent (DES), (1ChCl:2 EG), and for the first time a bright zinc coating has been achieved when NA was used. In metal electroplating processes, small-molecule additives are often included in the plating bath to improve properties of coating such as brightness, roughness, thickness, hardness and resistance to corrosion. The effects of additives on the electrodeposition of Zn from aqueous solution have been extensively investigated. However, very few studies have considered the effects of additives on the electrodeposition of Zn from ionic liquids or deep eutectic solvents. The electrochemical properties of the plating liquid have been studied here using cyclic voltammetry, chronocoulometry, chronoamperometry and microgravimetry (EQCM). Redox peak currents decrease when additives were included in the Zn solution and total charge was also reduced in experiments where additives were present. The Zn deposition in the absence of additive is in good agreement with an instantaneous growth mechanism at short experimental time scales (being indeterminate over longer periods), however, this changes to one of a progressive growth mechanism when additives were included in the coating bath. The current efficiency of zinc deposition in the DES without additives was 95%, which was reduced when additives were included. The resultant surface morphologies, thickness, topography, roughness and crystal structure of the Zn coating were revealed by scanning electron microscopy (SEM), atomic force microscopy (AFM) and X-ray diffraction (XRD), demonstrating that those additives serve as effective brighteners that can produce highly uniform and smooth zinc deposits.